“Se eu aprender, não vou ser um carro atolado no lugar”: trajetórias escolares de jovens no percurso para a EJA - Rodrigues, Flávia Covalesky de Souza (2021)
This work was developed in the Doctoral Course of the Graduate Program in Education at the Universidade Federal de Santa Maria, in the line of research “educational public policies, educational practices and their interfaces - LP2”. This is a study within the scope of Youth and Adult Education (EJA), with an emphasis on youth school trajectories and the social relevance of the modality as a space for schooling students with age/grade gaps before and during the COVID-19 pandemic. The guiding question of this research was: how do the school trajectories of young students develop in the transition from regular-time education to Youth and Adult Education? It had the general objective of analyzing the school trajectories of young students in the transition from regular-time education to Youth and Adult Education. To achieve it, the following specific objectives were proposed: to discuss public policies for the area of education regarding EJA and youth; to identify the profile of students who attend Elementary School at EJA in two municipal schools in Alegrete/RS; to comprehend the processes that lead the elementary school student to the Education of Youth and Adults on a regular basis through their school trajectories, and to understand how the school education of these students was conducted during the pandemic period of 2020. Qualitative-quantitative research of social analysis of the case study type was carried out. The subjects were EJA Elementary School students enrolled in two municipal schools in Alegrete, located in the state of Rio Grande do Sul. The data collection instruments used were a closed questionnaire and a semi-structured interview. Additionally, documentary research was used to structure aspects related to important legislation and quantitative data for the design of the studied panorama. The data obtained through the mentioned methodological instruments was treated from the qualitative textual analysis, developed by Moraes (2003) and Moraes and Galiazzi (2006; 2016). To support the theoretical discussions proposed here, I discussed with Paulo Freire (2018; 2017; 2001; 2000; 1999; 1987; 1985), Miguel Arroyo (2017; 2014; 2013), José Machado Pais (1993; 1990), Juarez Dayrell (2016; 2007; 2006), Raewyn Connell (2006), François Dubet (2020; 2015; 2007; 2005; 2004), Gimeno Sacristán (2017; 2016; 2013), Roque Moraes (2003; 2006; 2016), among other authors positioned in the socio-critical perspective. Through this study, it was possible to reveal that EJA, as it is organized, does not contribute to the social and educational demands of the present, nor does it collaborate in the construction of projects for the future of youths. Additionally, it indicates the difficulty of youths in age/grade gap to find adequate space within the schooling process available in the researched context.